Return migration of adult Atlantic salmon (Salmo salar L.) to northern Norway. (18th September 2017) - Ulvan, Eva Marita; Foldvik, Anders; Jensen, Arne Johan; Finstad, Bengt; Thorstad, Eva Bonsak; Rikardsen, Audun Håvard; Næsje, Tor Fredrik; ,
Abstract: The return migration of adult Atlantic salmon was investigated by analysing recaptures of individuals tagged and released as smolts in the River Altaelva and the River Halselva using a catch per unit effort approach. Although the salmon were recaptured over a large area along the coastline (from >1100 km south to > 500 km northeast of their home rivers), the results indicated a relatively accurate homeward navigation for most individuals. The straying rate to rivers other than the home river was 9%. Multi-sea-winter salmon returned earlier in the season than one-sea-winter salmon, but the geographical distribution of recaptures did not differ. Recaptures were equally distributed north and south of the home rivers, implying that salmon were arriving to the coast both north and south of their home rivers and that they may have returned from different ocean areas. This was supported by the fact that several salmon were recaptured in both the southern and northern parts of the North Atlantic Ocean, including at the Faroes, south coast of Greenland, Svalbard and in the Barents Sea. This study supports the hypothesis that the coastal phase of the natal homing in migrating fish species is neither passive nor guided by currents alone.